Inspection of empty bottle crates at bottling assembly lines - Del Carpio, Jorge (2003)
The bottling companies, to the entrance of their production line receive boxes with their respective bottles coming from the distributors, those that are not always the correct ones or they have certain type of abnormalities like they can be bottles of another type, broken bottles, other strange objects as glasses, plastics, etc. The observed problem that it can cause anomalies to the system that is due to the lack of an appropriate system of detection of flaws. At the moment in many production lines the inspection is carried out in a visual way. To solve these inconveniences an automatic system of detection of flaws it has been developed by means of the prosecution of images. The system consist of analogical camera, a card analog/digital and a development software.